AVAILABILITY VERSUS PERFORMANCE - Fiorini, Pierre M.; Lipsky, Lester (International Journal of Computing, 2014)
We discuss analytic procedures for evaluating the availability of parallel computer systems comprised of P processors with N tasks subject to failures and repairs. In addition, we argue, via analytic and numeric examples, that not incorporating the task-stream into the model is an inadequate approach for evaluating system performance.